Korelasi antara Self-Efficacy dan Berpikir Kreatif Matematis terhadap Kemampuan Spasial Peserta Didik - Vallencia, Vallencia; Bistari, Bistari; Rustam, Rustam (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2026)
Finding out how senior high school students' spatial abilities relate to their self-efficacy and mathematical creativity is the primary goal of this study. The purpose of this research was to identify the factors that affect students' spatial ability, with an emphasis on mathematical creativity and self-efficacy. The researchers in this study employed a correlational research design and quantitative approach. Maranatha Christian High School twelfth graders (n=96) were the subjects of the study, from which 37 were selected at random. A spatial ability test, a math creative thinking exam, and a self-efficacy questionnaire were the instruments used. Two methods that are often used for analyzing data are multiple correlation and Pearson product-moment correlation. First, the study found that there is a strong positive correlation between self-efficacy and spatial ability (Pearson Product-moment correlation = 0.809, > 0.325), and second, there is a strong positive correlation between mathematical creativity and spatial ability (Pearson Product-Moment correlation = 0.647, > 0.325). The multiple correlation coefficient for self-efficacy and mathematical creativity in relation to spatial ability is 0.809. This suggests a strong and favorable link. Future research may further explore variable relationships through qualitative analysis and improved, more specific instruments.